ANALISIS IMPLEMENTASI PASAL 6 AYAT (2) HURUF A PERATURAN DAERAH NOMOR 11 TAHUN 2009 TENTANG PENYELENGGARAAN ADMINISTRASI KESEKRETARIATAN DPRD (Studi Kasus Di DPRD Provinsi Lampung) - Ikhsan Erwin; Iskandar Agus (KEADILAN PROGRESIF, 2022)
The administration of the Lampung Province Regional Government, in accordance with the provisions of the Provincial DPRD Legislation, has a function, namely the establishment of a Provincial Regulation, a budget function and a supervisory function. The three functions are carried out as their main duties as representatives of the people. In the context of representing the people in the Province.The problem in this research is the implementation of Article 6 paragraph (2) Letter A Regional Regulation Number 11 of 2009 concerning the Implementation of Secretarial Administration in the Lampung Provincial DPRD and the inhibiting factors for the implementation of Article 6 paragraph (2) Letter A Regional Regulation Number 11 of 2009 concerning Administration Secretariat at DPRD Lampung Province. The research method uses a normative juridical approach and an empirical approach using secondary data and primary data, then qualitative juridical data analysis is carried out.The results of the research, the implementation of Article 6 paragraph (2) Letter A Regional Regulation Number 11 of 2009 concerning the Implementation of Secretariat Administration in the DPRD based on the medium-term development plan of the Lampung Province and then outlined in the strategic plan of the Lampung Provincial DPRD secretariat. The RPJMD document and the Lampung Provincial DPRD secretariat strategic plan contain the vision, mission, goals, objectives and target indicators. And the factors that hinder the performance of the Lampung Provincial DPRD Secretariat in carrying out secretarial administration are that the inhibitingfactors are, among others: 1. Lack of availability of adequate work facilities and infrastructure in supporting the implementation of main tasks and functions. 2. Limited skilled Human Resources (HR) in accordance with their field of work. Suggestion, In not being involved in carrying out their duties and functions in accordance with the laws and regulations, it is necessary to have sanctions given to individuals for accountability for actions that neglect them.